Greater Emotional Gain from Giving in Older Adults: Age-Related Positivity Bias in Charitable Giving - Bjälkebring, Pär; Västfjäll, Daniel; Dickert, Stephan; Slovic, Paul (Frontiers in Psychology, 2016)
Older adults have been shown to avoid negative and prefer positive information to a higher extent than younger adults. This positivity bias influences their information processing as well as decision-making. We investigate age-related positivity bias in charitable giving in two studies. In Study 1 we examine motivational factors in monetary donations, while Study 2 focuses on the emotional effect of actual monetary donations. In Study 1, participants (n=353, age range 20-74 years) were asked to rate their affect towards a person in need and then state how much money they would be willing to donate to help this person. In Study 2, participants (n=108, age range 19-89) were asked to rate their affect towards a donation made a few days prior. Regression analysis was used to investigate whether or not the positivity bias influences the relationship between affect and donations. In Study 1, we found that older adults felt more sympathy and compassion and were less motivated by negative affect when compared to younger adults, who were motivated by both negative and positive affect. In Study 2, we found that the level of positive emotional reactions from monetary donations was higher in older participants compared to younger participants. We find support for an age-related positivity bias in charitable giving. This is true for motivation to make a future donation, as well as affective thinking about a previous donation. We conclude that older adults draw more positive affect from both the planning and outcome of monetary donations and hence benefit more from engaging in monetary charity than their younger counterparts.